Hegemony of Sulinggih on Ngaben Ceremony towards Modernization Era in Bali - Puspa, Ida Ayu Tary; Saitya, Ida Bagus Subrahmaniam (Journal of Posthumanism, 2025)
The hegemony of the Sulinggih or priest in the Ngaben ceremony in the era of modernization is an interesting phenomenon to study. As a spiritual leader in the Balinese Hindu tradition, the Sulinggih has a central role in the implementation of rituals, including Ngaben. However, along with the development of the era, there has been a shift in the practice and meaning of this ceremony due to the influence of modernization. This study aims to analyze how the hegemony of the Sulinggih in the Ngaben ceremony is maintained or changes amidst the social, economic, and cultural dynamics of Balinese society. Using a qualitative approach and ethnographic methods, this study explores how the authority of the Sulinggih in this ceremony is perceived by the community, as well as how adaptations are made in the face of changing times. The results of the study show that although modernization brings various changes, the authority of the Sulinggih remains strong in the social and religious structure, despite negotiating with economic and technological factors.